2021
DOI: 10.1097/jfn.0000000000000316
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Self-Care Management as Persons Prepare to Reintegrate Into the Community

Abstract: Introduction Persons reentering the community after incarceration often confront a range of challenges that influence their ability to engage in self-care. This study sought to gain insight and understanding of how persons recently released from an incarceration experience perceive their preparedness for reentry and how this affects their ability to engage in self-care management. Method Using focus group methodology, four male, two female, and one mixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
1
6
0
1
Order By: Relevance
“…This accords with Maruca et al. (2021), who in their study of self‐care skills and reintegration after imprisonment, note that cooking for oneself and eating well were regarded by people leaving prison as one of the most important aspects of self‐care that they could acquire. Our study suggests that there is an interest and enthusiasm among some men living in prison to undertake food work for themselves whilst in prison which could build these skills in anticipation of release; our data have shown how some are keen to plan, shop, prepare, cook and serve food for themselves and others.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This accords with Maruca et al. (2021), who in their study of self‐care skills and reintegration after imprisonment, note that cooking for oneself and eating well were regarded by people leaving prison as one of the most important aspects of self‐care that they could acquire. Our study suggests that there is an interest and enthusiasm among some men living in prison to undertake food work for themselves whilst in prison which could build these skills in anticipation of release; our data have shown how some are keen to plan, shop, prepare, cook and serve food for themselves and others.…”
Section: Discussionsupporting
confidence: 78%
“…All the food work is done for them, and people living in prison are largely passive recipients of their food. Other research has suggested that passivity around consumptive choices can make individuals feel infantilised (Smoyer & Lopes, 2017), whereas active participation in food work can upskill individuals in preparation for reintegration and provide productive activity while in prison (Earle, 2018; Earle & Phillips, 2012; Maruca et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Five articles (8.6%) included innovative service delivery models such as electronic or digital treatment modalities ( Aronson et al, 2017 ) and mobile vans that administered MOUD ( Krawczyk et al, 2019 ). Finally, eight articles (13.8%) focused on other interventions such as civil commitment ( Christopher et al, 2018 ), an expedited Medicaid enrollment program ( Gertner et al, 2019 ), and self-care management ( Maruca et al, 2021 ). Appendix B displays relevant information for each study including more detailed information on interventions and outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Woodall et al, ( 2014 ) point to a paradox that highlights the fact that reintegration requires those in custody to exercise some agency, control and choice but many experiences in prison constrain these. In their study of the significance of self-care skills to reintegration after imprisonment, Maruca et al, ( 2021 ) note that cooking for oneself and eating well were regarded by prisoners as one of the most important aspects of self-care on release. Rather than simply focus on prison food as good nutrition for an underserved population, the findings of our synthesis suggest that integrating cooking and sharing food into the everyday routine of prison life (Dooris, 2009 ) can “strengthen the resources available to people and empower[s] them to increase control over the determinants of health and to thrive” (Dooris et al, 2014 , p.13).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that beyond adequate nutrition, food carries meanings in prison which can affect an individual’s personhood. Food matters in prison because interactions around food, which are characterised by top-down control and lack of choice, can augment feelings of distance from home (Comfort, 2008 ), impact an individual’s sense of autonomy (Smoyer & Kjaer Minke, 2015 ) and affect the potential of those in custody to reintegrate and care for themselves after imprisonment (Maruca et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%